Monitoring Cholera Transmission in Zambia Using the Cholera Elimination Scorecard - Caroline C. Chisenga; Lilian Lamba; Charlie C. Luchen; Ashley Duncan; Nyuma Mbewe; Masuzyo Zyambo; Maisa Kasanga; Fraser Liswaniso; Harriet Ng’ombe; Michelo Simuyandi; Amanda K. Debes; Roma Chilengi; et al. (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. We used the cholera elimination scorecard to better understand the changing cholera patterns in Zambia. The method used surveillance data from the Zambia National Public Health Institute to identify districts that had eliminated cholera or continued to be endemic between 2015 and 2024. Between 2017 and 2022 the number of cholera-endemic districts decreased from 27 to 6; however, in 2023 and 2024, a severe outbreak occurred in Lusaka and expanded to neighboring districts. Concurrently, a separate outbreak occurred in the northern areas of Zambia. We found the cholera elimination scorecard to be a practical and simple to use tool to understand changes in cholera transmission, including identifying persistently endemic districts and districts that had relapsed after having eliminated cholera. We suggest that the cholera elimination scorecard can supplement the Priority Areas for Multisectoral Interventions methodology for countries attempting to eliminate cholera.